Structure of the crust and the lithosphere beneath the southern Puna plateau from teleseismic receiver functions - Heit, B. (2014)
We present a teleseismic P and S receiver function study using data from a temporary passive-source seismic array in the southernmost Puna plateau and adjacent regions. The P receiver function images show the distribution of crustal thickness and Vp/Vs ratio for this area. Over much of the southern Puna plateau, the crustal thickness is 50–55 km, whereas to the west a thicker crust (∼60 to 75 km) is observed beneath much of the Andean volcanic arc region. From the Puna southward, there is little obvious change in the crustal thickness across the border of the plateau (south of 28°S). The crust is seen to progressively thin towards the east in the Pampean Ranges where it is 35–40 km thick. The southern Puna plateau is characterized overall by a low crustal Vp/Vs ratio (less than 1.70), implying a felsic crustal composition. An anomalously high Vp/Vs ratio of 1.87 is observed beneath the Cerro Galan volcanic center, in the region where a prominent crustal low-velocity zone identified below ∼10 km depth probably extends into the lower crust. The crustal thickness determined under the Cerro Galan area (59 km) is close to that of the rest of the southern Puna. The prominent high Vp/Vs ratio and low-velocity zone beneath the Galan region implies the presence of a zone of partial melt or a magma chamber is consistent with hypothesis calling for lithospheric delamination beneath the Galan caldera. A widespread crustal low-velocity layer observed beneath much of the southern Puna, correlates well with crustal low-velocity anomalies observed by teleseismic tomography. The lithosphere–asthenosphere boundary beneath the array can be clearly observed by both P and S receiver functions at depths of 70–90 km in agreement with previous studies suggesting a thin lithosphere beneath the high elevated plateau. The mantle transition zone discontinuities appear at expected depths.